'Passionate and professional': reconciling logics in public service accounting. Issue 2 (23rd February 2018) - Butler, Clare; Haynes, Kathryn
Abstract : In order to deliver public value, the UK government sought to build relationships and connect 'the public' with public servants (including back-office workers), but with what effect? Drawing on interviews with public service accountants, the authors found that how these accountants conceptualized 'the public'—as society or people—shaped whether public value was considered as a monetary or moral concept. Accountants who regarded the public as people spoke of an improper level of involvement and struggled to maintain their professionalism.